2022
DOI: 10.1071/an22155
|View full text |Cite
|
Sign up to set email alerts
|

Organic side streams (bioproducts) as substrate for black soldier fly (

Abstract: The growing world population accompanied by urbanisation and improved economies has resulted in an increased demand for diets rich in animal proteins. The rearing of livestock by existing practices is also becoming increasingly difficult due to changing environmental conditions. The use of black soldier fly larvae (BSFL) grown on organic side streams (bioproducts) as feed for animals presents a sustainable alternative to conventional feed ingredients. The nutritional and compositional profile of BSFL reared on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…However, to safely utilise these substrates, it is imperative to establish quality-assurance measures (EFSA 2015;FAO 2021). The utilisation of excreta, processed waste containing animal matter, and various other organic side streams as feed for BSFL rearing is prohibited in some countries, such as USA, Canada, and those within the European Union (EU) (Alagappan et al 2022). Regulations regarding the use of BSFL as animal feed state that, by default, insects cannot be directly employed as feed for other farmed animals (Żuk-Gołaszewska et al 2022).…”
Section: Rearing Methodsmentioning
confidence: 99%
“…However, to safely utilise these substrates, it is imperative to establish quality-assurance measures (EFSA 2015;FAO 2021). The utilisation of excreta, processed waste containing animal matter, and various other organic side streams as feed for BSFL rearing is prohibited in some countries, such as USA, Canada, and those within the European Union (EU) (Alagappan et al 2022). Regulations regarding the use of BSFL as animal feed state that, by default, insects cannot be directly employed as feed for other farmed animals (Żuk-Gołaszewska et al 2022).…”
Section: Rearing Methodsmentioning
confidence: 99%
“…Among other chemical contaminants, BSFL were found to accumulate mineral oil and some other hydrocarbons but none exceeding legal limits [ 47 ]. In general, BSFL are not considered to accumulate dioxins, polychlorinated biphenyls, or polycyclic aromatic hydrocarbons, and they do not accumulate and, at times, they even degrade many pharmaceuticals and pesticides [ 7 , 49 , 50 , 60 , 61 , 62 , 63 , 64 ]. One study found that substrate contaminated with malathion did affect BSFL negatively, but that study did not assess the impact of BSFL on the malathion levels in the residue or the prepupae [ 65 ].…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity increased if multiple compounds were in the substrate at the same time, or if synergists like piperonyl butoxide were added. Prior work suggests BSFL have high tolerance to aflatoxins and other mycotoxins and do not bioaccumulate them [ 49 , 51 , 60 , 68 , 69 , 70 ] though some may persist in their gut contents. While some plant toxins, like genotoxic pyrrolizidine alkaloids (PAs) and tropane alkaloids, were degraded from the substrate during BSFL bioconversion, others bioaccumulated in the larvae at varying rates: high for europine, rinderine and echinatine and very low for most other PAs and atropine and scopolamine [ 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the idea of upscaling and commercialising this product in the feed industry is limited due to several challenges associated with legal and production requirements. 29,30 One of the important challenges in production is to ensure that the BSFL reared on organic side streams are sufficient in nutritional composition to be used as animal feed. 31 The use of conventional methods to determine the nutritional composition can be time consuming and laborious.…”
Section: Introductionmentioning
confidence: 99%
“…BSFL, overall possess the ability to serve as a sustainable feed source in livestock production. However, the idea of upscaling and commercialising this product in the feed industry is limited due to several challenges associated with legal and production requirements 29,30 . One of the important challenges in production is to ensure that the BSFL reared on organic side streams are sufficient in nutritional composition to be used as animal feed 31 .…”
Section: Introductionmentioning
confidence: 99%